World of Flower Blue Pop Chalee : an artistic biography - Cesa, Margaret (Santa Fe Red Crane Books, 1997)
Pop Chalee was one of the first Native American woman artists to achieve national fame, recognition and commercial success. The author Margaret Cesa takes us back to the beginnings of this remarkable woman, born in 1906 in the drab mining town of Castlegate, Utah. Pop's mother, Merea Margherete Luenberger, was from Berne, Switzerland. Her father was Joe Lujan of Taos Pueblo
91364
Keywords: Pop Chalee -- 1906-; Tigua women; Indian women artists -- New Mexico -- Taos Pueblo; Indian women artists -- New Mexico -- Santa Fe